Risk management for a tailings re-mining project in Ghana. Issue 2 (7th April 2015) - Famiyeh, Samuel; Adaku, Ebenezer; Kissi-Mensah, Laud; Amoatey, Charles Teye
Abstract : Purpose: – Proper risk management is a critical requirement for the success of every project. This is, to a large extent, due to the role risk plays in determining project outcomes. The mining sector usually is linked with high environmental, social and economic risks. Hence, the process of systematic risk management applied to a single case study of a tailings re-mining project in Ghana holds the potential for invaluable insights on risk management in the mining sector. The paper aims to discuss these issues. Design/methodology/approach: – Mining organization experts were asked to identify project risks, and 50 staff from the organization were invited to make subjective assessments of the probability of occurrence and consequences for each of 15 identified risks. From this assessment, a risk severity matrix was developed. Findings: – The findings show that the most severe risks for a tailings re-mining project include spillage caused by leakage from pipes; vandalism by illegal mining operators; late deliveries of mining materials; the effect of rainfall; and failure to gain project approval from the Environmental Protection Agency. Risk treatment options are suggested for these risks. Research limitations/implications: – The study is limited to only the risk issues associated with tailings re-mining projects. Practical implications: – Practically, this study highlights for mining companies and operators, the critical risks factors that militate against successful tailings re-mining projects. Social implications: – This study, essentially, reveals the threat of illegal mining operations to such an important project and hence the need for strong security to avoid such threats. Originality/value: – This study contributes to the debate on the risk factors that affect tailings re-mining, especially, from a developing country's point of view.